Printing of Wool and Cotton Fabrics with Natural Dyes - Ibrahim Bahtiyari, Muhammed; Benli, Huseyin; Yavas, Arzu (Asian Journal of Chemistry, 2013)
Natural dyes are the heritage of the history to human being. Although they were used for the colouration of goods from the ancient time, it is not common to use natural dyes commercially now. But at least in some special goods it is saving its popularities too. On the other hand, it can be foreseen that the demand on the ecological, natural and organic products in all consumable articles will make natural dyes popular again. Owing to this, it is important to continue the studies on the usability of natural dyes in textile colouration techniques. This study is focused on the printing of natural dyes differently on dyeing with natural dyes. For this aim four different natural sources were used. For the printing process, pigment printing was selected and the printing was managed on wool and cotton fabrics without use of any mordants. The colour values and the fastnesses of prints were evaluated. It was observed that the natural dyes can be used in pigment printing processes and different colour values with different fastnesses could be observed.